Pandangan Jhon Chrysostom tentang kualifikasi Seorang Imam: Refleksi Komparatif Buku The Priesthood dan 1 Timotius 3:1-7 - Halawa, Desti Ratna Sari (Sekolah Tinggi Teologi IKAT Jakarta, 2021)
Being a priest or pastor suddenly who only studied the Bible for 3 months is an issue that is considered a problem in the church environment. Priests play a role in guiding the congregation to gain salvation, know God and have a soul that is increasingly purified from day a day. In carrying out this role there are conditions that must be possessed so that in his ministry, he becomes a priest who succeeds in shepherding the souls entrusted by God. For this reason, this study aims to provide an overview of the qualifications of a priest in the book The Priesthood and in 1 Timothy 3: 1-7. Through a literary analysis of The Priesthood and 1 Timothy 3: 1-7 the writer will explore the requirements for becoming a priest. The data collected will help the priests to be more serious in their ministry. According to Chrysostom the priest should not be a chaplain of the priestly office, have a clear mind, not be seduced by worldly desires, not be angry, not a person who loves praise. Meanwhile, according to the apostle Paul, the priest must be able to accept the responsibility of shepherding the church, have self-control, capable of teaching, be recognized as dignified in the family, well known in the community. The two opinions of this figure mutually support the success of a priest in pure service to the congregation. The result is that the priest fulfills the requirements to become a priest, so the priest can successfully serve the souls of the congregation that God has entrusted to him.Â AbstrakMenjadi imam atau pendeta secara tiba â€“ tiba, yang hanya belajar Alkitab 3 bulan, merupakan isu yang dianggap sebagai persoalan dalam lingkungan gereja. Imam berperan dalam membimbing jemaat untuk memperoleh keselamatan, mengenal Allah dan memiliki jiwa yang semakin dimurnikan dari hari lepas hari. Dalam menjalankan peran ini ada syarat yang harus dimiliki sehingga dalam pelayanannya, ia menjadi seorang imam yang berhasil menggembalakan jiwa- jiwa yang dipercayakan Tuhan. Untuk itu, penelitian ini bertujuan untuk memberikan gambaran kualifikasi seorang imam dalam buku The Priesthood dan dalam surat 1 Timotius 3: 1-7. Melalui analisis pustaka Buku The Priesthood dan surat 1 Timotius 3: 1- 7 penulis akan mengexplorasi syarat-syarat menjadi imam. Data- data yang dikumpulkan akan menolong para imam untuk semakin serius dalam pelayanannya. Menurut Chrysostom imam harus bukan seorang pengejar jabatan keimaman, memiliki pikiran yang jernih, tidak tergoda dengan keinginan duniawi, bukan pemarah, bukan orang yang cinta akan pujian. Sedangkan menurut rasul Paulus imam itu harus Jiwanya sanggup menerima tanggung jawab penggembalaan jemaat, mengontrol diri, cakap mengajar, dikenal berwibawa dalam keluarga, dikenal baik di tengah masyarakat. Kedua pendapat tokoh ini saling mendukung keberhasilan seorang imam dalam pelayanan yang murni kepada jemaat. Hasilnya, memenuhi syarat menjadi imam adalah panduan seorang imam untuk mencapai keberhasilan melayani jiwaâ€“jiwa atau jemaat yang dipercayakan Tuhan kepadanya.